PENGARUH KUALITAS PRODUK, PERSEPSI HARGA, DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DI RUMAH MAKAN BEBEK KALEO TEBET JAKARTA SELATAN DIMASA PANDEMI COVID 19 - Heidi Reza Ruliarto (LPPM Universitas Asa Indonesia, 2020)
This study aims to analyze the influence of the effect of product quality, price perception, and quality of service on customer satisfaction in Bebek kaleo tebet south jakarta in pandemic covid 19. In this sample research respondents used were Bebek Kaleo Customers consisting of 80 respondents, by Accidental Sampling. The analysis technique uses multiple linear regression. Value of partial correlation coefficient the Product Quality variable with Consumer satisfaction is 0.207, which means that there is a real but weak relationship between the Product Quality variable and the Partial Customer Satisfaction, the Price variable with Customer Satisfaction is 0.084 meaning there is no relationship, but simultaneously very weak, the Service Quality variable with consumer satisfaction is 0.584 means that there is a significant and strong influence between the variable service quality and customer satisfaction partially. Simultaneously, Product Quality, Price Perception, Service Quality have an effect on Customer Satisfaction by 73.7%, while the remaining 26.3% is influenced by other factors.